Cover Picture: Effect of Spinel Inversion on (CoxFe1−x)3O4 All‐Oxide Solar Cell Performance (Energy Technol. 7/2016). Issue 7 (15th June 2016) - Yan, Zhi; Keller, David A.; Rietwyk, Kevin J.; Barad, Hannah‐Noa; Majhi, Koushik; Ginsburg, Adam; Anderson, Assaf Y.; Zaban, Arie
Abstract : Solid Results on All‐Solid Solar Cells : The cover picture shows Co–Fe–O: a material for a new type of all‐oxide solar cell, which reaches its maximum photovoltaic performances at a particular Fe:Co ratio. If enough iron is added to Co3 O4, the structure changes from spinel, a stable phase of Co3 O4, to inverse spinel, which alters the physical properties and results in an improvement in the photovoltaic performance. The performance then begins to drop if too much iron is added to the structure. This study demonstrates the power of combinatorial materials science for solar cell design. More details can be found in the Full Paper by Zhi Yan and Arie Zaban et al. from Bar Ilan University onpage 809 in Issue 7, 2016 (DOI:10.1002/ente.201500402 ).